Akselerasi UMKM Lokal: Strategi Digitalisasi Pemasaran dan Penguatan Branding di Kelurahan Pinang Mancung - Bobby Hartanto; Rapat Piter Sony Hutauruk; Benhart Nainggolan; Christin Natalia Sianipar; Tina Herianty Masitah; Asnahwati Asnahwati; Benny Ardianto Sinaga; Sofia Purnama Simanjuntak; Ella Astri Dayanti (Community Service Progress, 2026)
Pinang Mancung Village, Tebing Tinggi City, has significant agricultural potential, which supports the growth of various local Micro, Small, and Medium Enterprises (MSMEs) such as Roti Kacang Doa Ibu, Kerupuk Tempe AAY, and Keripik Singkong Aira. Despite having quality products, MSMEs face classic challenges in the form of a lack of understanding of modern marketing, financial management, and weak product branding. Many business actors do not even have a basic visual identity such as a banner or logo. This Community Service Program (KKN) aims to empower and develop the quality of MSMEs through two main strategies: strengthening physical branding and initiating digital marketing. The implementation method used is participatory mentoring, which includes MSME mapping surveys, socialization, and direct execution. The results of this community service activity are: (1) Provision of branding assets in the form of new banners for MSMEs Roti Kacang Doa Ibu and Kerupuk Tempe AAY, as well as the creation of a logo for MSME Dara Frozen Food; (2) Initiating digital marketing through the Facebook platform; (3) Creation of supporting facilities at the sub-district office, including a reflexology path, a Toga garden, and a "Cultivate the 7K" sign. This program has successfully increased the visibility and professional image of MSMEs and provided business owners with an initial understanding of the importance of online marketing.